2011
DOI: 10.1097/grf.0b013e318236e18b
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma in Pregnancy

Abstract: Since the early 1950s clinicians have been concerned about the impact of pregnancy on malignant melanoma (MM). Case reports and case series described a grave prognosis for women diagnosed with MM during pregnancy. Today MM in pregnancy takes on enhanced significance as more women delay childbearing into their 30s and 40s, and the incidence of MM during pregnancy may be expected to increase. In addition, relative immunosuppression during pregnancy theoretically may favor the potential for MMs to behave more agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 21 publications
0
53
0
Order By: Relevance
“…Contrary to this finding, another in vitro study demonstrated that tamoxifen significantly hindered cell invasion in melanoma; in addition, it was found that, apart from melanoma, breast, esophageal, pancreatic, lung, gastric and colorectal cancers and soft tissue sarcomas exhibited the same female survival advantage (18). Neither melanoma diagnosed during pregnancy was found to affect survival rate, nor the pregnancy that occurred before or after the diagnosis of melanoma was shown to affect the survival outcome of melanoma; furthermore, oral contraceptive use and hormone replacement therapies were not found to be associated with increased risk of melanoma development and/or prognosis (19). In the present study, we were unable to assess the definitive role of sex hormones in melanoma, due to relevant information (such as menopausal status or oral contraceptive use of the study group) missing from our data, which was defined as another limitation of this study.…”
Section: Univariate Analyses Multivariate Analyses ------------------mentioning
confidence: 89%
“…Contrary to this finding, another in vitro study demonstrated that tamoxifen significantly hindered cell invasion in melanoma; in addition, it was found that, apart from melanoma, breast, esophageal, pancreatic, lung, gastric and colorectal cancers and soft tissue sarcomas exhibited the same female survival advantage (18). Neither melanoma diagnosed during pregnancy was found to affect survival rate, nor the pregnancy that occurred before or after the diagnosis of melanoma was shown to affect the survival outcome of melanoma; furthermore, oral contraceptive use and hormone replacement therapies were not found to be associated with increased risk of melanoma development and/or prognosis (19). In the present study, we were unable to assess the definitive role of sex hormones in melanoma, due to relevant information (such as menopausal status or oral contraceptive use of the study group) missing from our data, which was defined as another limitation of this study.…”
Section: Univariate Analyses Multivariate Analyses ------------------mentioning
confidence: 89%
“…Others larger multivariate analyses, however, demonstrated that it was equally strong in pre-as well as in post-menopausal groups [20]. Parallely, the literature concerning melanoma progression in pregnancy is also controversial [21][22][23][24], although several recent reports demonstrate that pregnancyassociated melanomas have poorer outcomes than other melanomas [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 95%
“…Others larger multivariate analyses, however, demonstrated that it was equally strong in pre-as well as in post-menopausal groups [20]. Parallely, the literature concerning melanoma progression in pregnancy is also controversial [21][22][23][24], although several recent reports demonstrate that pregnancyassociated melanomas have poorer outcomes than other melanomas [25][26][27][28][29].In vitro progesterone influences melanoma growth [30][31][32][33], but several melanoma cell lines have been studied and very different experimental protocols have been used, so that the results actually available in literature are not univocal. Further research on this topic is thus needed, especially in view of the widespread use of PG in clinical practice.…”
mentioning
confidence: 95%